Stocking impact and temporal stability of genetic composition in a brackish northern pike population (Esox lucius L.), assessed using microsatellite DNA analysis of historical and contemporary samples - Larsen, P F; Hansen, M M; Nielsen, E E; Jensen, L F; Loeschcke, V (Heredity, 2005)
During the last decade, brackish northern pike populations in Denmark have been subject to stocking programmes, using nonindigenous pike from freshwater lakes, in order to compensate for drastic population declines. The present study was designed to investigate the genetic impact of stocking freshwater pike into a brackish pike population in Stege Nor, Denmark. We analysed polymorphism at eight microsatellite loci in samples representing the indigenous Stege Nor population prior to stocking (ie from 1956 to 1957), along with a sample of the contemporary Stege Nor population and samples from the three populations used for stocking. Despite large numbers of stocked fry, the results from both individual and population level admixture analyses demonstrated extremely poor performance and <1% introgression of stocked freshwater pike into the brackish pike population. Furthermore, pairwise F ST estimates between samples demonstrated close genetic relationship among temporal samples from Stege Nor, indicating temporal stability over the last 45 years. We also estimated the effective population size ( N e ) of pike in Stege Nor and applied a test for recent population bottlenecks. The harmonic mean of N e was relatively high (>250), but there were indications of bottlenecks in all samples and populations. We ascribe this finding to historical rather than recent bottlenecks, possibly dating back to founder events associated with postglacial recolonisation.